1982
DOI: 10.1017/s0016672300020966
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of the lac-PTS system ofKlebsiella

Abstract: SummaryThe isolation of a temperature sensitivepts Imutant which fails to utilize lactose provides strong evidence thatKlebsiellastrain CT-1 utilizes lactose via a phosphoenolpyruvate dependent lactose-phosphotransferase system (PTS-lac). We designate this lactose utilization systemeluforevolved lactose utilization. Analysis of a series ofLac−mutants identifies two genes,eluAandeluB, whose function is required for lactose utilization by this pathway. The functions specified by these genes are not known, but ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1985
1985
2001
2001

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…For instance, lactose is transported in S. aureus by enzyme IlLac (242) but by a proton symport system in the family Enterobacteriaceae (135). Furthermore, the same strain (e.g., strains of K. pneumoniae growing rapidly on lactose) may have a plasmid-encoded IlLac in addition to the proton symport system encoded on the chromosome (see reference 127).…”
Section: The Pts: An Overviewmentioning
confidence: 99%
“…For instance, lactose is transported in S. aureus by enzyme IlLac (242) but by a proton symport system in the family Enterobacteriaceae (135). Furthermore, the same strain (e.g., strains of K. pneumoniae growing rapidly on lactose) may have a plasmid-encoded IlLac in addition to the proton symport system encoded on the chromosome (see reference 127).…”
Section: The Pts: An Overviewmentioning
confidence: 99%
“…For (8). In Klebsiella aerogenes, lactose uptake can be catalyzed both via the PTS and via a non-PTS lactose permease (5). Recently, it was suggested that cellobiose uptake in Erwinia chrysanthemi is also PTS mediated (1).…”
mentioning
confidence: 99%